Strategi Peningkatan Kapasitas Modal Sosial dan Kualitas Sumberdaya Manusia Pendamping Pengembangan Masyarakat - D. Susanto (Institut Pertanian Bogor, 2010)
Based on normal situation effective and successful community development are indicated by severalevidence, namely: improvement of welfare state of the whole segments of the community, development ofsocial trust, improvement of awareness of the community with regard to their potentials, their real needs,their problems in achieving their needs, and getting alternatives of solution to break their problems byutilizing their potentials, people are innovated to get better lives, and finally their have great motivationto be self reliance and develop more inter-dependency with other systems. To obtain such qualifiedcommunity development the role of so-called as partners or insider and outsider change agents of thecommunity is absolutely needed. Commonly, the community cannot sharply know themselves very well.They need somebodies, insider and or outsider individuals who professionally have potentials andcompetencies to develop them in such, that through working together they may achieve better lives. Thecommunity partners in development are those individuals who have prepared themselves through variouslearning processes, who ideally have unique characteristics such as: high empathy, highly care to others,sensitive, have qualified personality, have highly capability to utilize their senses, have highly capabilityin communication, and very consistent in talking and doing which the community are eager to trust andexpress their needs. But unfortunately, based on field studies done by several doctorate candidates showthat the partners of the community on development have not possessed such high qualification. Most ofthem in some district areas in Jawa and outer Jawa Island need more training to improve their socialcapital capacity, and their quality of human resources as well. Consequently, we need smart anddiliguent strategy on how to improve competencies of the partners of the community development throughlearning processes in such, that sooner or later their roles will provide positive impact on the bettermentof quality of life of the community.